L’éducation en vue d’un développement durable dans la formation des enseignants en Suisse : entre directives ministérielles et mises en œuvre pratiques - Francine Pellaud; François Bourqui; Bertrand Gremaud; Lionel Rolle (VertigO)
By presenting the Swiss school system and its specificities concerning education for sustainable development, this article discusses the theoretical foundations of that education. It also presents the concrete avenues offered to students of the Haute école pédagogique (HEP) of Fribourg, responsible for the training of future primary school teachers in this township. An important role in the abovementioned system is played by an interdisciplinary approach, which occupies a key position in the new compulsory curriculum in the French speaking part of Switzerland. For interdisciplinarity to become more than a declaration of good intentions, the measures taken by the HEP’s didactics of science and education for sustainable development research unit have been twofold : to incorporate this approach as a basis for the entire teaching program and to recommend it as an institutional project. Subdivided in four complementary parts, this article presents a comprehensive overview of the position occupied by education for sustainable development and interdisciplinarity in the current school system, and their progressive integration that spans from the official administrative guidelines to the training of future teachers.